Differential var gene expression in the organs of patients dying of falciparum malaria - Montgomery, Jacqui (Blackwell Publishing Ltd, 2007)
Sequestration of parasitized erythrocytes in the microcirculation of tissues is thought to be important in the pathogenesis of severe falciparum malaria. A major variant surface antigen, var/Plasmodium falciparum erythrocyte membrane protein 1, expressed on the surface of the infected erythrocyte, mediates cytoadherence to vascular endothelium. To address the question of tissue-specific accumulation of variant types, we used the unique resource generated by the clinicopathological study of fatal paediatric malaria in Blantyre, Malawi, to analyse var gene transcription in patients dying with falciparum malaria. Despite up to 102 different var genes being expressed by P. falciparum populations in a single host, only one to two of these genes were expressed at high levels in the brains and hearts of these patients. These major var types differed between organs. However, identical var types were expressed in the brains of multiple patients from a single malaria season. These results provide the first evidence of organ-specific accumulation of P. falciparum variant types and suggest that parasitized erythrocytes can exhibit preferential binding in the body, supporting the hypothesis of cytoadherence-linked pathogenesis.